EVALUATION OF AN ANTI-DANDRUFF SHAMPOO INCORPORATING ETHANOL EXTRACT FROM CORN SILK (ZEA MAYS L.) AGAINST CANDIDA ALBICANS FUNGUS: FORMULATION AND ACTIVITY ASSESSMENT - LENY; SARI, MELIA; GINTING, MANDIKE; MELISA; ISKANDAR, BENNI (International Journal of Applied Pharmaceutics, 2024)
Objective: The aim of this study was to investigate the effectiveness of corn silk (Zea mays L.) extract as an antifungal ingredient in shampoo formulation for treating dandruff caused by Candida albicans. Methods: Plant identification, sampling, preparation of simplisia, phytochemical screening, simplisia characterization, ethanol extraction of corn silk, and the formulation of shampoos with extract concentrations of 5%, 10%, and 15%, alongside blank and positive controls. The formulations underwent physical evaluation, irritation testing, and antifungal activity testing using the disc diffusion method. Results: The corn silk shampoo formulations were stable during storage, non-irritating, was in thick liquid form with yellowish to brown colour, corn scent, had pH between 5.0-5.8, foaming capacity at 10.3-13.0 cm, with the viscocity ranging 1967-2224 cPs, means it met the required standards for shampoo formulation and characterization. Antifungal testing revealed inhibition zone diameters of 0 mm for the blank (F0), 7.87 mm for F1 (5%), 9.46 mm for F2 (10%), 15.89 mm for F3 (15%), and 18.71 mm for the positive control (C+), with a one-way ANOVA test indicating a significant difference compared to the negative control. Conclusion: Corn silk extract could be effectively formulated into an antifungal shampoo, with the 15% concentration being the most effective against Candida albicans, highlighting its potential as a natural ingredient for anti-dandruff shampoos.